Special Features of Changeability of Daily Sum of Precipitation in Tbilisi in 1957-2006 - Amiranashvili, Avtandil G. (Journals of Georgian Geophysical Society, 2016)
Wide-ranging studies of contemporary climate change in Georgia were begun in 1996 and they continue on the present time. First of all the inventory of greenhouse gases in Georgia was carried out, spatial-temporary variations in the fields of temperature, precipitation, cloudiness, aerosol air pollution, surface cover and other climate-forming parameters were studied. Later there have been begun works on forecasting of air temperature and precipitation change in some region of Georgia. In particular results of detailed statistical analysis of the average semi-annual and annual values of precipitation in Tbilisi for the period 1957-2006 are presented earlier. In the indicated period of time the weak positive trend of precipitation in the cold period of year was observed. A trend of precipitation for warm half-year periods was not observed. For a yearthe weak tendency of an increase of the precipitation was observed. In this work, which presents the continuation of the foregoing studies, some results of the standard statistical analysis of observational data of the Hydrometeorological department of Georgia of daily sum of precipitation (DSP) in Tbilisi in 1957-2006are represented. Thus, the statistical structure of atmospheric precipitation with daily intensity of 0.1-2, 2.1-5, 5.1-15, 15.1-30 and >30 mm and annual quantity of days without and with precipitation for the ten five-year time intervals from 1957-1961, 1962-1966,…, to 2002-2006 is studied. The weak positive and positive trend of DSP respectively for the ranges of 5.1-15 and 15.1-30 mm was observed. The negative and weak negative trend of DSP respectively for the ranges of 0.1-2 and 2.1-5 mm was observed. The trend of DSP with an intensity of >30 mm was not observed.